(untitled) (Fiep Bulletin - online, 2013)
The objective of this research was to characterize the psychomotor development of students of both sexes, with 7 years old and from public schools of Montes Claros city. The research is descriptive e comparative, with qualitative and quantitative approach and cross-sectional. The sample was composed by 60 children of both sexes, with normal weight, overweight and obesity. The selection of sample was of intentional way for children with overweight and obesity, but randomly for children with normal weight. It was used the Psychomotor Battery of Vitor da Fonseca. The research was approved by Ethics Committee of “Universidade Estadual de Montes Claros – Unimontes”. The statistical procedures were descriptive analysis of data, average, standard deviation and percentage. Were used the t test of student and ANOVA, with the level of significance of p?0.05. It was concluded in the results that total sample has Eupraxic (EPX) development in factors tonicity, equilibrium and global praxis; with Dyspraxic (DPX) development in factors body idea, time-space structuration and slim praxis; and Apraxic (APX) development in lateralization. Between children with normal and with overweight BMI, were not found differences statistically significant. It is conclude that classification of general psychomotor development of group was Eupraxic profile, being that the factors more affected were slim praxis and lateralization.